2017
DOI: 10.1017/wsc.2017.6
|View full text |Cite
|
Sign up to set email alerts
|

Cross-resistance Patterns to Acetyl-CoA Carboxylase Inhibitors Associated with Different Mutations in Japanese Foxtail (Alopecurus japonicus)

Abstract: Japanese foxtail is a grass weed in eastern China. This weed is controlled by fenoxaprop-P-ethyl, one of the most common acetyl-CoA carboxylase (ACCase)-inhibiting herbicides. Some Japanese foxtail populations have developed resistance to fenoxaprop-P-ethyl, owing to target-site mutations (amino acid substitutions) located within the carboxyl transferase domain of ACCase. In the present study, three mutations were detected in three fenoxaprop-P-ethyl–resistant Japanese foxtail populations: Ile-1781-Leu in JCJT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Unfortunately, only a very limited number of weeds resistant to ACCase inhibitors in South America have had the resistance mechanism elucidated such as E. indica . Cross-resistance to herbicides that act under the same MoA is usually caused by TSR mechanisms (Beckie et al, 2012;Chen et al, 2017), even though recent evidence indicates the importance of NTSR in conferring cross-resistance (Iwakami et al, 2019). Several authors have reported weeds manifesting crossresistance to different ACCase-inhibiting herbicides, including those arising from mutations Ile1781Leu, Ile2041Asn, and Trp2027Cys (Chen et al, 2017).…”
Section: Target Site Resistance (Tsr)mentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, only a very limited number of weeds resistant to ACCase inhibitors in South America have had the resistance mechanism elucidated such as E. indica . Cross-resistance to herbicides that act under the same MoA is usually caused by TSR mechanisms (Beckie et al, 2012;Chen et al, 2017), even though recent evidence indicates the importance of NTSR in conferring cross-resistance (Iwakami et al, 2019). Several authors have reported weeds manifesting crossresistance to different ACCase-inhibiting herbicides, including those arising from mutations Ile1781Leu, Ile2041Asn, and Trp2027Cys (Chen et al, 2017).…”
Section: Target Site Resistance (Tsr)mentioning
confidence: 99%
“…Cross-resistance to herbicides that act under the same MoA is usually caused by TSR mechanisms (Beckie et al, 2012;Chen et al, 2017), even though recent evidence indicates the importance of NTSR in conferring cross-resistance (Iwakami et al, 2019). Several authors have reported weeds manifesting crossresistance to different ACCase-inhibiting herbicides, including those arising from mutations Ile1781Leu, Ile2041Asn, and Trp2027Cys (Chen et al, 2017). In addition to the mutations Asp2078Gly and Cys2088Arg conferring broad spectrum of resistance on all classes of ACCase-inhibiting herbicides (Yu et al, 2007;Délye et al, 2008;Kaundun, 2010;Scarabel et al, 2011;Cruz-Hipolito et al, 2011;Gherekhloo et al, 2012;Kaundun et al, 2012), resistance levels are not solely dependent upon amino acid substitutions.…”
Section: Target Site Resistance (Tsr)mentioning
confidence: 99%
See 1 more Smart Citation
“…ACCase resistance was first reported in Beckmannia syzigachne in 2014 and many farmers shifted to ALS inhibitors such as mesosulfuron‐methyl for the control of ACCase‐resistant weeds . This, in turn, led to multiple‐resistance in B. syzigachne and A. japonicus . Current estimates are that nearly 10% of the area in the Chinese provinces of Anhui and Jiangsu are under serious threat of resistance to both ACCase and ALS inhibitors across all key grasses, and farmers are once again shifting herbicide use to PSII inhibitors …”
Section: Herbicide Resistance In Asiamentioning
confidence: 99%
“…23 This, in turn, led to multiple-resistance in B. syzigachne and A. japonicus. 21,24,25 Current estimates are that nearly 10% of the area in the Chinese provinces of Anhui and Jiangsu are under serious threat of resistance to both ACCase and ALS inhibitors across all key grasses, and farmers are once again shifting herbicide use to PSII inhibitors. 21 Maize production is spread across Asia, with even smaller countries such as Vietnam and Thailand planting over 1 × 10 6 ha annually.…”
Section: Herbicide Resistance In Asiamentioning
confidence: 99%